Immunotherapy for ocular myasthenia gravis: an observational study in Japan - Tomoko Narita; Shunya Nakane; Akiko Nagaishi; Naoya Minami; Masaaki Niino; Naoki Kawaguchi; Hiroyuki Murai; Jun-ichi Kira; Jun Shimizu; Kazuo Iwasa; Hiroaki Yoshikawa; Yuki Hatanaka; et al. (Therapeutic Advances in Neurological Disorders, 2023)
Background: Treatment for ocular myasthenia gravis (OMG) has not yet been well established. Few reports have been published on the clinical practice and outcomes of OMG. Objectives: We investigated treatment of OMG and its outcomes in Japan. Design: We performed a retrospective cross-sectional survey of OMG patients from eight hospitals in Japan. Methods: Clinical information, including sex, age at onset, initial symptoms, autoantibodies, clinical course, treatment history, complications, and outcomes, was obtained. In addition, we recorded the total number of patients with MG and OMG separately. Results: In total, 135 patients with OMG (67 men, 68 women) were included. Treatment of OMG was not simple and involved various immunotherapeutic strategies. Eight patients went into remission spontaneously without immunotherapy. A total of 117 patients showed improvements after treatment, whereas 10 patients showed refractory responses to treatment. Overall outcomes were good; however, symptoms persisted in 60.7% of patients even after treatment. Among 90 patients who received immunotherapy, only two showed a refractory response. Meanwhile, for 45 patients who did not receive immunotherapy, 8 were refractory. Thus, the rate of refractory disease in the group with immunotherapy was significantly lower ( p  = 0.001, u-test) than in the group without immunotherapy. The proportion of generalized MG patients among all MG cases was low in medical centers where immunotherapy for OMG was frequently performed. Conclusion: Although the overall prognosis for patients with OMG was good, symptoms remained in more than half of the patients. Immunotherapy, including corticosteroids, may be beneficial for patients with OMG. Plain language summary Is immunosuppressive therapy beneficial for myasthenia gravis patients with ocular symptoms only? Patients with ocular myasthenia gravis (OMG) have only eye symptoms for more than 2 years. Whether this condition is an initial stage of the disease before eventually progressing to generalized myasthenia gravis (gMG) is still uncertain. Different from gMG, OMG is not life-threatening. But eye symptoms often cause troublesome problems in life. Doctors have treated OMG patients similarly to patients with gMG. There is no standard clinical practice for OMG. In this study, we examined how patients with OMG were treated at eight different specialist centers in Japan. In 135 patients with OMG, 8 patients became symptom free without treatment, 117 patients showed improvements after treatment, whereas 10 patients did not get well. Overall outcomes were good, but symptoms remained in 60.7% of patients even after treatment. Among 90 patients who received one or more immunotherapies, only 2 did not get well. Meanwhile, for 45 patients who did not receive immunotherapy, 8 remained ill. We found that treatment of OMG was not simple and often needed multiple immunotherapies. Administering immunotherapy, including corticosteroids, may be beneficial for patients with OMG.